(untitled) (DAPesquisa, 2020)
This text presents performative research as a practical and creative study methodology in an academic master’s research based on the dialogues of the body. We share here the initial ongoing research processes in which Jacques Lecoq’s bodily pedagogical procedures are studied for the scenic artist known as Seven Levels. We present how performative research embraces our propositions for the practical studies carried out and also for the construction of writing that emanates from research laboratories, built through a logbook. The performative research here is understood according to the precepts of Brad Haseman (2015) and also of Brazilian researchers and artists who developed their studies in this perspective, such as Ciane Fernandes (2014).